Nitrogen or phosphorus repletion strategies for enhancing lipid or carotenoid production from Tetraselmis marina. (August 2017) - Dahmen-Ben Moussa, Ines; Chtourou, Haifa; Karray, Fatma; Sayadi, Sami; Dhouib, Abdelhafidh
Highlights: A two-stage process was applied to enhance the lipid productivity of T. marina . Phosphorus and nitrogen depletion resulted in the lowest lipid productivity from T. marina. N repletion enhanced both the cell growth and lipid content for biodiesel production. P repletion increased both carotenoid and the fraction of PUFA. Two-stage N and P-stress change the H2 O2, TBARS level and SOD activity of T. marina . Abstract: The objective of this study was to investigate the accumulation of lipid and photosynthetic pigments from Tetraselmis marina . When the cells were grown in F/2-medium for seven days in the first stage, the carotenoid and lipid contents, and productivity were 44 g/kg (DW), 27% and 31 mg/L/d, respectively. After second stage of cultivation of T. marina for further 3-days under N-replete condition (4.41 mM NaNO3 ) increased biomass concentration of 1900 mg/L and lipid content of 50% were observed, with an enhanced lipid productivity of 86.36 mg/L/d and SFA and MUFA fractions of 70.76 and 13.14%, respectively. However, under P-repletion (2.08 mM NaH2 PO4 ), its carotenoid content increased to 89.23 g/kg and its PUFA for 65% of total lipids. Results showed that N and P-replete conditions decreased SOD activity and increased H2 O2 and TBARS levels of T. marina . Thus, this native microalga strain could be a potent candidate for feed, food or biofuel production.